Magnetic resonance imaging appearances of the Mirena and GyneFix intra-uterine contraceptive devices: A report of two cases. Issue 4 (1st October 2000) - Hall, Glen H; Guthrie, Kate A; Turnbull, Lindsay W
Abstract : We report here two cases which illustrate the magnetic resonance imaging (MRI) appearance of the Mirena levonorgestrel releasing intra-uterine system and the GyneFix copper intra-uterine contraceptive implant. The MRI appearance of these devices has not to our knowledge been reported to date, and as increasing numbers of women choose to use these devices for treatment of gynaecological conditions and contraception, it becomes increasingly important to recognise their appearance on pelvic imaging.